Avaliação das condições de cultivo e criopreservação sobre o estabelecimento de linhagens fibroblásticas de onças-pintadas, panthera onca (linnaeus, 1758) - Silva, Maria Bárbara (Universidade Federal Rural do Semi-Árido, 2020)
The increasingly small population quantity of jaguars, associated with their ecological importance, has resulted in the development of strategies that promote their conservation. In this sense, somatic cells derived from the skin of these animals can be used for this purpose, either in the production of clone embryos, in obtaining cells induced to pluripotency and in genetic studies of the species. Thus, the proper establishment of these samples is an initial step for these applications. Therefore, the aim of the present study was to assess the damage caused by in vitro culture and cryopreservation conditions on the establishment of five fibroblast lines derived from adult jaguars. Thus, fragments of skin from the apical auricular region of one female and four males were cultured in vitro to obtain somatic cells. Initially, to identify the cell type, cells were confirmed as fibroblasts after morphological and immunofluorescence analysis, and the five strains (one animal/one line) were subjected to two experiments. In the first experiment, cells were evaluated in different culture passages (first, third, tenth) for viability, metabolism and proliferative activity. In the second experiment, cryopreserved cells were evaluated for viability, metabolism, proliferative activity, levels of reactive oxygen species (ROSs), mitochondrial membrane potential (ΔΨm) and apoptosis after thawing and one, three and ten culture passages. Noncryopreserved cells were used as controls. The in vitro culture after the first (26.1 h ± 4.9), third (22.9 h ± 1.6) and tenth passage (22.8 h ± 3.7) and cryopreservation (30.0 h ± 1.4) did not affect proliferative activity. Moreover, no difference was observed for viability after the first (98.9% ± 0.8), third (92.5% ± 6.2), tenth (95.7% ± 1.4) passage and cryopreservation (73.2% ± 9.8). Nevertheless, cells cultured to the tenth passage (49.0% ± 3.3) and cryopreserved (32.7% ± 2.8) reduced their metabolism. Additionally, cryopreserved cells showed high levels of ROS (1.4 ± 0.1) and altered ΔΨm (0.9 ± 0.0) in arbitrary fluorescence units, when compared to non-cryopreserved cells (1.0 ± 0.1 and 1.0 ± 0.2). Finally, cryopreserved cells and cultured after ten passages reduced the reduced proliferative activity (45.1% ± 12.0) and number of viable cells (30.4% ± 5.7), when compared to cryopreserved and cultured cells after one and three passages. In conclusion, viable fibroblasts can be established from jaguars’ ears and that although these cells have not shown changes in viability and proliferative activity, they suffer damage during a long culture and cryopreservation under the studied conditions
Keywords: Felídeos silvestres; Bancos de células somáticas; Linhagem celular; Wild felids; Somatic cell banking; Cell lin; CIENCIAS AGRARIAS::MEDICINA VETERINARIA